Theorizing the Body: Developing a Framework for Understanding the Body in Online Learning Environments - Jennifer H. Kelland (Adult Education Research Conference, 2006)
This paper examines how five elements of the body (physical, personal, political, knowledgeable and expressive) have been understood in face-to-face learning contexts and how they could be examined in online learning contexts to create inclusive learning environments.
Keywords: Online learning; body; identity; relationships; inclusivity